2020
DOI: 10.2337/db19-0550
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Fatty Acid and Its Metabolite 18-HEPE Ameliorate Retinal Neuronal Cell Dysfunction by Enhancing Müller BDNF in Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is a widespread visionthreatening disease, and neuroretinal abnormality should be considered as an important problem. Brain-derived neurotrophic factor (BDNF) has recently been considered as a possible treatment to prevent DR-induced neuroretinal damage, but how BDNF is upregulated in DR remains unclear. We found an increase in hydrogen peroxide (H 2 O 2 ) in the vitreous of patients with DR. We confirmed that human retinal endothelial cells secreted H 2 O 2 by high glucose, and H 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…A single EPA administration improved vascular endothelial function in type 2 diabetic Otsuka Long-Evans Tokushima fatty rats by inhibiting ERK, decreasing NF-κB activation, and reducing COX-2 expression [ 164 ]. In addition, oral EPA administration alleviated retinal neurodegeneration via BDNF in Müller glia cells in the early DR stages [ 162 ]. Clinically, a randomized controlled trial conducted in patients with diabetic macular edema (DME), which was induced by ROS and DR inflammation, found that the combined administration of oral DHA and intravitreal anti-VEGF significantly improved DME compared with a single treatment with anti-VEGF drugs.…”
Section: Pathology Of Diabetic Retinopathy (Dr) and Its Relationshmentioning
confidence: 99%
“…A single EPA administration improved vascular endothelial function in type 2 diabetic Otsuka Long-Evans Tokushima fatty rats by inhibiting ERK, decreasing NF-κB activation, and reducing COX-2 expression [ 164 ]. In addition, oral EPA administration alleviated retinal neurodegeneration via BDNF in Müller glia cells in the early DR stages [ 162 ]. Clinically, a randomized controlled trial conducted in patients with diabetic macular edema (DME), which was induced by ROS and DR inflammation, found that the combined administration of oral DHA and intravitreal anti-VEGF significantly improved DME compared with a single treatment with anti-VEGF drugs.…”
Section: Pathology Of Diabetic Retinopathy (Dr) and Its Relationshmentioning
confidence: 99%
“…1 DM is associated with severe damage to multiple organ systems, such as the heart, eyes, and kidneys. [2][3][4] Recently, increasing attention has been paid to the pathological changes in the brain induced by DM. Diabetes-induced brain injury manifests as neurodegeneration, cerebral infarction, and progressive cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of reactive oxygen species (ROS) is considered to be a factor in which inflammation of the gingiva affected diabetic retinopathy [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Porphyromonas gingivalis ( P. gingivalis ) and Fusobacterium nucleatum ( F .…”
Section: Discussionmentioning
confidence: 99%
“…Overproduced ROS in the oral cavity can cause oxidative stress and oxidative damage to cells, proteins, and lipids throughout the body, which can lead to systemic disease [ 31 ]. Oxidative stress has been shown to reduce neuroretinal function [ 32 ]. In addition, oxidative stress has been found to be associated with the accelerated onset of diabetic retinopathy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%